Navigating Arctic Waters: A Summary of Ship Activities and Ice-Ship Interactions in Alaskan Waters - Peel, Grant J (author); Gedikli, Ersegun D (author); Hendrikse, H. (author) (POAC, 2023)
Climate change is affecting global weather patterns, but nowhere is this more apparent than in the Arctic. The Arctic is an extreme environment going through rapid climate change, resulting in the opening of new shipping lanes and leading to less multiyear ice formation. This increases the risk of collision with the sea ice making it difficult to make long term voyage plans based on sea ice predictions. The Automatic Identification System (AIS) provides important services for marine domain awareness. For safe and effective ship traffic management and the development of new artificial intelligence (AI) marine algorithms, precise AIS readings for hull size and type are typically required. In this paper, we provide a summary of ship activities as well as relevant ice information in Alaskan waters that may result in ice-ship interactions and discuss them. AIS ship data was used to determine the ship speed distribution in different areas in the Alaskan waters. Ship movement in ice infested regions was compared with sea ice data from the Copernicus Reanalysis Products and sea ice thickness was estimated using empirical equations to identify potential ship-sea ice interactions. Data from 2015 to 2020 was analyzed to determine if there is an increase in maritime activity that can be linked to a decline in sea ice extent in Alaskan waters. The AIS data was also sorted by ship hull types to see how the different sectors of the Alaskan maritime industry are changing over time in ice-covered areas. Offshore Engineering